4D Aliphatic photopolymer polycarbonates as direct ink writing of biodegradable, conductive graphite‐composite materials. Issue 10 (14th July 2021) - Brooks, Scott; Cartwright, Zachary; Merckle, David; Weems, Andrew C.
Abstract: Photopolymers are one of the fastest growing 3D printing material classes, despite the lack of diversity in performance or composition. A simple addition of graphite nanopowder is explored for tailoring aliphatic polycarbonate performance and enhancing advanced material properties, targeting the mechanical performance of the norbornene‐containing poly(norbornene trimethyl carbonate) using poly(trimethyl propane allyl ether carbonate) for thermoset formation using thiol‐ene photochemistry. A 30 wt% graphite‐composite photopolymer ink displays shear thinning behavior suitable for pneumatic direct ink write (DIW) printing, along with enhanced elastic modulus (15–542 MPa) and an increase in ultimate strength (2–22 MPa for the composite ink) without significant variation in the glass transition temperature. The composites are further demonstrated as 4D materials including shape memory, conductivity, and recyclability, with this work serving as a guide for designing DIW inks from photopolymer resins. Abstract :